The Influence of Psychological Pricing, Brand Awareness and Promotional Media on Purchasing Decisions for Mineral Water Products - Ali Imran (Journal of Social Science and Business Studies, 2023)
This research aims to determine the influence of psychological pricing, brand awareness, and promotional media on decisions to purchase mineral water. In this research, the quantitative descriptive method was used. In this research, the data collection method used is the survey research method. Data collection was carried out by distributing questionnaires online via Google Form to 30 people. Judging from the research results, it can be seen that there is no influence between psychological pricing, brand awareness, and promotional media on purchasing decisions. Psychological pricing can have a significant influence on student purchasing decisions. Prices that end with a lower number tend to make the product appear more affordable and attractive to consumers. This pricing strategy can influence the perceived value of the product and generate incentives to purchase mineral water. Brand awareness of available mineral water also influences students' purchasing decisions. If students have good knowledge about a particular brand of mineral water being sold, they are more likely to choose that brand because they have higher trust and familiarity with that brand. The promotional media used to market mineral water products also plays a role in influencing students' purchasing decisions. If you use effective promotional media such as television advertisements, social media, or attractive brochures, you can attract students' attention and influence them to choose the mineral water products being sold.